Step
*
1
2
2
1
of Lemma
rmul-distrib1
1. x : ℝ
2. y : ℝ
3. z : ℝ
4. bdd-diff(reg-seq-list-add([x * y; x * z]);reg-seq-list-add([reg-seq-mul(x;y); reg-seq-mul(x;z)]))
5. n : ℕ+
6. r1 : {r:ℤ| |r| < |2 * n|} 
7. (((y n) + (z n) + 0) * (x n) rem 2 * n) = r1 ∈ {r:ℤ| |r| < |2 * n|} 
8. r2 : {r:ℤ| |r| < |2 * n|} 
9. ((x n) * (y n) rem 2 * n) = r2 ∈ {r:ℤ| |r| < |2 * n|} 
10. r3 : {r:ℤ| |r| < |2 * n|} 
11. ((x n) * (z n) rem 2 * n) = r3 ∈ {r:ℤ| |r| < |2 * n|} 
⊢ |((-1) * r1) + r2 + r3| ≤ (3 * |2 * n|)
BY
{ ((RWO "minus-one-mul<" 0 THENA Auto) THEN (RWW "int-triangle-inequality absval_sym<" 0 THENA Auto)) }
1
1. x : ℝ
2. y : ℝ
3. z : ℝ
4. bdd-diff(reg-seq-list-add([x * y; x * z]);reg-seq-list-add([reg-seq-mul(x;y); reg-seq-mul(x;z)]))
5. n : ℕ+
6. r1 : {r:ℤ| |r| < |2 * n|} 
7. (((y n) + (z n) + 0) * (x n) rem 2 * n) = r1 ∈ {r:ℤ| |r| < |2 * n|} 
8. r2 : {r:ℤ| |r| < |2 * n|} 
9. ((x n) * (y n) rem 2 * n) = r2 ∈ {r:ℤ| |r| < |2 * n|} 
10. r3 : {r:ℤ| |r| < |2 * n|} 
11. ((x n) * (z n) rem 2 * n) = r3 ∈ {r:ℤ| |r| < |2 * n|} 
⊢ (|r1| + |r2| + |r3|) ≤ (3 * |2 * n|)
Latex:
Latex:
1.  x  :  \mBbbR{}
2.  y  :  \mBbbR{}
3.  z  :  \mBbbR{}
4.  bdd-diff(reg-seq-list-add([x  *  y;  x  *  z]);reg-seq-list-add([reg-seq-mul(x;y);  reg-seq-mul(x;z)]))
5.  n  :  \mBbbN{}\msupplus{}
6.  r1  :  \{r:\mBbbZ{}|  |r|  <  |2  *  n|\} 
7.  (((y  n)  +  (z  n)  +  0)  *  (x  n)  rem  2  *  n)  =  r1
8.  r2  :  \{r:\mBbbZ{}|  |r|  <  |2  *  n|\} 
9.  ((x  n)  *  (y  n)  rem  2  *  n)  =  r2
10.  r3  :  \{r:\mBbbZ{}|  |r|  <  |2  *  n|\} 
11.  ((x  n)  *  (z  n)  rem  2  *  n)  =  r3
\mvdash{}  |((-1)  *  r1)  +  r2  +  r3|  \mleq{}  (3  *  |2  *  n|)
By
Latex:
((RWO  "minus-one-mul<"  0  THENA  Auto)  THEN  (RWW  "int-triangle-inequality  absval\_sym<"  0  THENA  Auto))
Home
Index